The Role of Internal Audit on the Effectiveness of the Internal Control System at KSP Kopdit Pintu Air - Yonivasius Siga; Henrikus Herdi; Yosefina Andia Dekrita (Neo Journal of economy and social humanities, 2024)
This study aims to determine the role of internal audit on the effectiveness of the internal control system at KSP Kopdit Pintu Air. In this study, the author uses a qualitative descriptive type of research. The resource persons in this study are employees in the internal control system section of KSP Kopdit Pintu Air and also from the cooperative supervisory element. The results of the study show that the internal audit of KSP Kopdit Pintu Air has carried out its role by the steps to implement the audit in ISO 9001, namely conducting audit planning, audit process, reporting audit results, and follow-up on audit results. In carrying out the audit process, several aspects are the main focus of the internal audit of KSP Kopdit Pintu Air, including aspects of governance, risk profile, financial performance, and capital.